2004
DOI: 10.1161/01.cir.0000130162.11925.21
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind, Randomized Controlled Trial on the Effect of Leukocyte-Depleted Erythrocyte Transfusions in Cardiac Valve Surgery

Abstract: Background-Leukocytes in allogeneic blood transfusions are believed to be the cause of immunomodulatory events. A few trials on leukocyte removal from transfusions in cardiac surgery have been conducted, and they showed inconclusive results. We found in a previous study a decrease in mortality rates and number of infections in a subgroup of more heavily transfused patients. Methods and Results-Patients (nϭ496) undergoing valve surgery (with or without CABG) were randomly assigned in a double-blind fashion to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
183
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(191 citation statements)
references
References 20 publications
3
183
1
4
Order By: Relevance
“…Through all randomized controlled trials only in cardiac surgery the findings were conclusive for a deleterious TRIM effect of WBC-containing RBCs with a higher short-term (up to three month post transfusion) mortality rate [69], [70], [71]. Though, even in this setting, the reasons for the excess deaths attributed to WBC-containing ABTs remain elusive.…”
Section: Clinical Studies On Transfusion-related Immunomodulationmentioning
confidence: 96%
“…Through all randomized controlled trials only in cardiac surgery the findings were conclusive for a deleterious TRIM effect of WBC-containing RBCs with a higher short-term (up to three month post transfusion) mortality rate [69], [70], [71]. Though, even in this setting, the reasons for the excess deaths attributed to WBC-containing ABTs remain elusive.…”
Section: Clinical Studies On Transfusion-related Immunomodulationmentioning
confidence: 96%
“…Erythrocyte transfusion causes immunomodulation, although its extension and deficiency type are variable [21]. Randomized clinical trials, analyzing ICU inpatients, demonstrated that the use of non-leukocyte-reduced erythrocyte concentrates leads to multiple organ failure and death in up to 10% of patients, against 5% in those who used leukocyte-reduced erythrocyte concentrates [22]. This is the complication most often associated with blood transfusion and lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental results have shown that allogeneic blood transfusion leads to immunomodulation in the recipient [27][28][29]. There is epidemiological evidence that TRIM facilitates the recurrence of malignancy or the occurrence of postoperative infections [30][31][32], although an association with fatal cancer occurrence has not been demonstrated. This condition might be similar to the phenomenon that high-dose immunosuppressive regimens, such as cyclosporine, in transplant recipients lead to a higher frequency of cancer mortality [33].…”
Section: Discussionmentioning
confidence: 99%